Percutaneous Nephrolithotomy of Kidney Calculi in Horseshoe Kidney - Maryam Zolfaghari (Urology Journal, 2007)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Tahoma; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:1627400839 -2147483648 8 0 66047 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} p.CharCharCharChar, li.CharCharCharChar, div.CharCharCharChar {mso-style-name:" Char Char Char Char"; mso-style-unhide:no; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:12.0pt; mso-line-height-rule:exactly; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Tahoma","sans-serif"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: The aim of this study was to evaluate percutaneous nephrolithotomy (PCNL) in horseshoe kidneys with calculi. Materials and Methods: Between 1995 and 2005, we performed PCNL in 9 patients with horseshoe kidney. In 3 of them, there was a single calculus and the rest had multiple calculi in the pelvis and at least 1 in the calyxes. Ultrasonography, plain abdominal radiography, and intravenous urography (IVU) were performed in all patients. We used fluoroscopy for entering the system and then, pneumatic or ultrasonic lithotripsy was used. Results: In all except 1 patient (88.9%) we could access the system. Single calculi in 3 patients were removed. In 5 patients with multiple calculi, the calculus causing obstruction was removed, and in 3, the calculi located in the calyxes were removed too. Consequently, 66.7% were stone-free at the end of the procedure. In 2 patients, there were residual calculi in the calyxes and they underwent candidates for extracorporeal shockwave lithotripsy. Conclusion: Percutaneous nephrolithotomy can be used in patients with horseshoe kidney if the patient selection is appropriate and the surgeon is experienced enough. The success rate and complications are the same as the patients with normal anatomy. However, access to the lower calyx is more difficult due to its anatomic status.